Nonlinear Analysis and Characterization of Piezoaeroelastic Energy Harvesters with Discontinuous Nonlinearities - Bouma, Adam (2022)
The effects of freeplay and multi-segmented nonlinearities in the pitch degree of freedom on the dynamical responses of a two-degree-of-freedom piezoaeroelastic energy harvesting system are investigated. The nonlinear governing equations of the considered piezoaeroelastic energy harvesting system are derived along with the use of the unsteady representation based on the Duhammel formulation to model the aerodynamic loads. The nonlinear piezoaeroelastic response is carried out in the presence of freeplay and multi-segmented nonlinearities before and after the linear onset of flutter. Such nonlinearities can be introduced to piezoaeroelastic energy harvesters for performance enhancement through the possible existence of sudden jumps and chaotic responses due to the grazing bifurcation. It is shown that the existence of discontinuous effects results in the possibility of harvesting energy at lower speeds than the linear onset speed of instability. Additionally, the increase of the strength of the multi-segmented nonlinearities leads to the presence of aperiodic responses with the presence of several bifurcations limiting the system’s dynamics at low pitch angles.